If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 = 2s + 2 Reorder the terms: 10 = 2 + 2s Solving 10 = 2 + 2s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-2s' to each side of the equation. 10 + -2s = 2 + 2s + -2s Combine like terms: 2s + -2s = 0 10 + -2s = 2 + 0 10 + -2s = 2 Add '-10' to each side of the equation. 10 + -10 + -2s = 2 + -10 Combine like terms: 10 + -10 = 0 0 + -2s = 2 + -10 -2s = 2 + -10 Combine like terms: 2 + -10 = -8 -2s = -8 Divide each side by '-2'. s = 4 Simplifying s = 4
| 6x-4(3x)+12=103-x | | 19=6+33t+-16t^2 | | D^4+D^2+4D+4=0 | | (4x-1)=56 | | 2(m-21)+4(m-3)=48 | | (7x+2)=(3x+-2) | | -3-m=-3 | | 2/3x-3=1/2x+4 | | 5g+10=3g+21 | | 5x+4=4x+8 | | 11p-4s+5r-3p+2s-r= | | -1w+4=3 | | 5x-42=3x+6 | | -7+u=-2 | | 4x+15=2x+6 | | -18=-3w | | 2(x+4)=6+x | | -1v+3=11 | | 5a+6b=-23 | | 3-3d=-3 | | 11-2z=1 | | 2(x-22)+3(x-3)=37 | | 173-v=284 | | 2x-9y-6x-8y+7z= | | 250+10=90b+12 | | 5=4p-11 | | 7d+14e= | | 2(2w-3)-8w= | | m=6/5,(8,-2) | | 5x+7=67-x | | X+(x+1)=189 | | 2x+3(5-4x)=15-10x |